Interface formation in magnesium/aluminium bimetallic castings with a nickel interlayer. (2nd September 2016) - Zhang, Hui; Li, Lingfeng; Chen, Yiqing; Luo, Alan A.; Liu, Lihua
Abstract : The natural oxide layer is an inherent barrier in interfacial bonding between aluminium (Al) and magnesium (Mg) alloys in Mg/Al bimetallic casting, resulting in insufficient wettability between the molten Mg and solid Al substrate during bimetallic casting processes. In this investigation, a 'zincate + nickelling' surface treatment has been developed for Al alloy 6061 substrate, replacing the oxide layer with a nickel coating. This procedure comprises a combined pickling/redox-reaction and nickelling process, which drastically improves the substrate's wettability with molten Mg. The bimetallic experiments conducted on a self-designed high-vacuum test apparatus provide valuable understanding of the interfacial phenomena of Mg/Al bimetallic castings. The test results show that the shear strength of bimetallic castings is significantly improved due to the fact that the formation of Mg–Al intermetallic compounds is impeded by a nickel coating. The potential corrosion problem associated with nickel additions could be addressed by an organic top coating for the bimetallic system.